UNVEILING FACTORS AFFECTING FIRM VALUE OF FOOD AND BEVERAGE COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Sylvia, Sylvia; Santioso, Linda (International Journal of Application on Economics and Business, 2025)
The objective of this research is to observe the relationship between factors affecting firm value as one of the important components in impacting investor investment decisions. The influencing factors include profitability, capital structure, and firm size. During this study, the purposive sampling method was utilized in food and beverage sub-sector companies registered on the Indonesia Stock Exchange. This method produces results in the form of 93 data samples from 31 companies during the period 2021 to 2023. By utilizing Eviews Software version 12, this study applies the multiple regression analysis method during testing. The findings obtained based on this study explain that there are two factors, such as profitability and capital structure, which can positively and significantly impact firm value. Meanwhile, firm size does not significantly affect firm value. From the results gathered, it is hoped that this study will be able to provide an impact and contribution to enriching knowledge related to the factors that influence firm value as a dependent variable. This study is likewise anticipated to make a substantial contribution by providing a profound understanding, while stimulating subsequent inquiries into the factors that may shape firm value. Not only that, this research can also contribute to giving references to related companies to be capable of producing more effective financial policies and decisions.